Binge Drinking Despite Consequences: The Role of Psychological Dysregulation. Issue 2 (4th March 2017) - Harris, Jennifer S.; Stewart, David G.; Krzyzaniak, Sheherezade L.; Charuhas, Julia P.; Moon, Kelsey C.; Holdren, Amber L.; Manuel, Jacob A.; Davis, Cristina L.; Joy, Sara A.
ABSTRACT: The relationship between binge drinking and alcohol-related consequences has been validated through research in several ways, yet adolescents continue to use alcohol in high quantities despite negative outcomes. Psychological dysregulation has been understood as a predisposing factor for adolescent use, but this research sought to investigate the role of affective, behavioral, and cognitive dysregulation as perpetuating factors. The current study examined psychological dysregulation as a mediator in the relationship between binge drinking and related consequences. One hundred twenty-three participants were referred by school administrators. Participants were given questionnaires to measure quantity of alcohol use, alcohol-related consequences, and psychological dysregulation. Conditional process found that psychological dysregulation mediated the relationship between binge drinking and consequences. An implication of this research is that adolescents continue to drink in high volumes despite negative outcomes because they are emotionally, behaviorally, and cognitively dysregulated. These disruptions may make it more difficult for them to utilize effective coping skills. This research provides important information to help researchers understand factors that not only predispose, but also perpetuate, adolescent binge drinking in adolescents. This information should be considered in the development of treatment methods in order to increase sustainability of outcomes.